2021
DOI: 10.3389/fphar.2021.700387
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Self-Assembled Gel for Gastric Endoscopic Submucosal Dissection-Induced Ulcer: A Preclinical Study in a Porcine Model

Abstract: Endoscopic submucosal dissection (ESD) is a routine procedure for the management of early gastrointestinal neoplasia, but it results in large ulcers. This study aims to examine the feasibility and effectiveness of a newly developed self-assembled gel on the ulcer healing process after ESD. Sixteen 2.0-cm (diameter) gastric ulcers were created by ESD in five pigs. All ulcers were randomized: control group (n = 7, routine ulcer management) and gel-treated group (n = 9). The gel was applied to cover the whole ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Gastric mucosal wound protective gel includes a colloidal solution and a fixative solution. The colloidal solution is mainly composed of sodium alginate and polylysine, and the fixative solution is a cationic compound solution [ 24 ]. The alkaline polylysine in colloid solution is electrically neutral and not cross-linked with sodium alginate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gastric mucosal wound protective gel includes a colloidal solution and a fixative solution. The colloidal solution is mainly composed of sodium alginate and polylysine, and the fixative solution is a cationic compound solution [ 24 ]. The alkaline polylysine in colloid solution is electrically neutral and not cross-linked with sodium alginate.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the polyurethane intestinal submucosal matrix hydrogel mainly accelerated wound healing by reducing the inflammatory response and promoting mucosal endothelial cell regeneration. Li et al [ 24 ] investigated a novel self-assembled hydrogel using an artificial ulcer model of gastric surgery in pigs. The results showed that the hydrogel could promote wound healing by promoting gastric mucosal endothelial hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations